(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Cupriavidus necator is a chemolithoautotrophic bacteria with high biotechnological relevance, particularly for bio-based production processes. Organic streams (whey) from the dairy industry, rich in proteins, sugars, and minerals, can serve as valuable sources of carbon and nitrogen for microbial growth [1]. This study evaluates the effect of redox reagent dithiothreitol (DTT) on bacterial growth, hydrogenase (Hyd) activity, and polyhydroxyalkanoate (PHA) accumulation in C. necator H16 cultured on acid whey (AW) and sweet whey (SW). Bacterial growth was monitored by measuring optical density at 600 nm (OD₆₀₀), and Hyd activity was quantified using hydrogen-dependent methylene blue reduction, while PHA accumulation was analyzed using high-performance liquid chromatography (HPLC) [2]. The results demonstrated enhanced bacterial growth in DTT-supplemented samples. The highest OD₆₀₀ was observed on day 5 for the AW+DTT culture (OD₆₀₀ = 5.1) and on 6th day for the SW+DTT culture (OD₆₀₀ = 4.6), 2 fold higher than their respective controls without DTT. Hyd activity was detected in all samples; however, its onset was earlier and more pronounced in DTT-treated cultures. The maximum Hyd activity reached 0.17 U/min/g CDW in the SW+DTT sample. PHA accumulation was observed during growth on both AW and SW. Interestingly, PHA levels decreased when Hyd activity was high, suggesting a possible inverse relationship between energy metabolism via hydrogen oxidation and carbon storage. In summary, supplementation with DTT enhances C. necator H16 growth on dairy side-streams, promotes earlier Hyd activation, and influences PHA accumulation dynamics. This approach highlights the potential of valorizing dairy industry by-products for sustainable microbial bioprocesses.